The Byzantine Garden. What to Plant in the Garden according to 12th Book of Geoponica by Cassianus Bassus? - Helbig, Maciej (Studia Ceranea, 2021)
The main aim of this paper is to analyse the text of the 12th book of Geoponica for the purpose of identification of vegetable plants, which were described by Cassianus Bassus. The analysis will serve as the first step for further inquiries that will include the reconstruction of recipes that require some of the vegetables presented in the text. The text of Geoponica is a basic source learn about the agriculture but also the culinary art of the Byzantine Empire, even though it is rather hard to read due to the complicated style and quite a large number of technical terms (i.e. botanical, agronomical or astrological to name just a few). As already mentioned, the first part of the analysis is to identify the plants mentioned by Bassus, which will allow me to take further steps, i.e. to reconstruct the culinary recipes, in which the plants mentioned by the Author can be found. Without this precise identification, the reconstruction of the recipes would not be possible at all. In the 12th book of his Geoponica Bassus gave descriptions of several plants that should be taken into consideration while planning the garden, mostly for their medicinal or cooking properties. Amongst them, Author mentioned garlic, artichoke, melon, leek, radish, celery, and cucumbers. Having the rather big number of plants narrowed down will allow to demonstrate in vivo how they were served according to De re coquinaria by Apicius and present the practical usage of vegetables proposed by Bassus for cultivation. As Apicius’ cookbook is the only one preserved from Antiquity, it will remain the major source of the recipes presented in this paper.